Evaluation of Antioxidant for Agaricus Bisporus and Different Strains of Pleurotus Ostreatus - Al-Jubori, Muna; A. Hassan , Abdullah; Al-Bahrani , Rusol (Iraqi Journal of Science, 2023)
Four mushrooms were used in the present study, Agaricus bisporus (B62) strain (Lelion, Varrains , France) , Pleurotus ostreatus (Blue grey-BG) and P. ostreatus (White oyster-WH) from Mushroom Box Company, United Kingdom, while P. ostreatus (P2) was the local fungus isolated and identified in this study. Radical scavenging activity of alcoholic extracts from mushrooms was found to be higher than those of aqueous extracts at the same concentration tested in all results in the present study and alcoholic extract for P. osteatus (P2) gave the highest result in concentration (25) mg/ml (60.53+0.55 %) in DPPH test , reducing power (5.4±0.1), total phenolic component (11.46+0.05) mg/g, chelating activity (75.86+16.95%) and antioxidant activity (86+0.1%), if concentration decreased the antioxidant activity decreased also. In aqueous extract(57.40+2.16%) in DPPH test, reducingpower (3.63+0.05), total phenolic component (7.20+0.10) mg/g, chelating activity (73.66+1.15%) and antioxidant activity (70.53+0.37%) for the same fungus and same concentration.